1993
DOI: 10.1002/pen.760332007
|View full text |Cite
|
Sign up to set email alerts
|

Orientational crystallization and orientational drawing as strengthening methods for polyethylene

Abstract: St. Petersburg 199004, Russia and V. A. MARIKHIN and L. P. MYASNIKOVA A. F. lo8e Physical Technical Institute Russian Academy of Sciences St. Petersburg 194021, RussiaThis paper reports on the theoretical and experimental studies of structure formation and strengthening (stiffening) of flexible-chain polymers. Two techniques of strengthening relying on the melt extrusion, i.e., orientational crystallization (crystallization initiated by melt extension) and drawing (uniaxial stretching of a crystallized polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Research on the formation of polymer networks can be traced back to the end of 1970s. 42,43 These pioneering attempts used MC simulations of lattice or CG models. Fully atomistic studies began in the mid-1990s when molecular force fields and computer power enabled such endeavors.…”
Section: Building Polymer Networkmentioning
confidence: 99%
“…Research on the formation of polymer networks can be traced back to the end of 1970s. 42,43 These pioneering attempts used MC simulations of lattice or CG models. Fully atomistic studies began in the mid-1990s when molecular force fields and computer power enabled such endeavors.…”
Section: Building Polymer Networkmentioning
confidence: 99%
“…The last step of the orienter is postcooling of the film with additional rollers. In the orientation process, the crystalline and amorphous regions are oriented, which enhances many film properties such as stiffness, tensile strength, optics (haze and gloss) and water vapor transmission rate (WVTR) [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…By increasing the annealing temperature, the segments of loose tie chains can be drawn into the crystallites, leading to thicker lamellae and higher overall degree of crystallinity. Elyashevich et al [111] suggested that higher annealing temperature results in narrower length distribution of tie chains, meaning that more stretched tie chains are produced in the inter-lamellar regions. Chen et al [110] also confirmed that the lamellae thickness increased with increasing annealing temperature up to the peak melting temperature, but higher temperature led to the formation of long-period lamellar spacing.…”
Section: Pe Membranesmentioning
confidence: 99%